Energy Management of Municipal Solid waste in the Context of Low Carbon Development - I. M. Potravny; D. Baah (Управленческие науки)
The paper comprehensively links the solution of the processing municipal solid waste (MSW) problem with the production of energy, the development of renewable energy and the greenhouse gas emissions reduction. There was determined being based on the analysis of global trends in the field of MSW management that the generation of energy from waste, the production of non-recyclable fractions of renewable energy on the basis of processing is an important direction of a low carbon economy and reducing the burden on the environment. There was carried out an ecological and economic assessment of the main technologies of thermal processing of MSW. The contribution of the implementation of investment projects for the construction of waste energy plants to the implementation of Russia's national goals in the field of waste management is shown in the Moscow region and Sochi. Taking into account the existing foreign experience, measures for financing and supporting investment projects for energy waste disposal were proposed: the introduction of a green tariff for MSW-to-energy processing facilities; the use of an investment incentive mechanism based on capacity supply agreements (PDMS); the implementation of an extended producer responsibility mechanism; state support measures; the attraction of green bonds; the use of equity and project financing methods, and quotas trading in greenhouse gas emissions. The practical significance of the research is to substantiate the possibility and necessity of developing and implementing investment projects for energy waste disposal, energy generation and reduction of greenhouse gas emissions.